2022
DOI: 10.1097/ta.0000000000003791
|View full text |Cite
|
Sign up to set email alerts
|

DeepBackRib: Deep learning to understand factors associated with readmissions after rib fractures

Abstract: BACKGROUND:Deep neural networks yield high predictive performance, yet obscure interpretability limits clinical applicability. We aimed to build an explainable deep neural network that elucidates factors associated with readmissions after rib fractures among nonelderly adults, termed DeepBackRib. We hypothesized that DeepBackRib could accurately predict readmissions and a game theoretic approach to elucidate how predictions are made would facilitate model explainability. METHODS:We queried the 2017 National Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…While physician experience is essential for providing high-quality clinical trauma care and treatment [ 19 , 20 ], information from various imaging modalities is also critical [ 21 , 22 , 23 ]. The goal of incorporating DL in trauma care is to hasten the diagnostic process, streamline therapeutic decision-making, and ultimately improve patient outcomes [ 24 , 25 ]. Therefore, it is crucial to develop an iterative DL algorithm that can be effectively implemented in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…While physician experience is essential for providing high-quality clinical trauma care and treatment [ 19 , 20 ], information from various imaging modalities is also critical [ 21 , 22 , 23 ]. The goal of incorporating DL in trauma care is to hasten the diagnostic process, streamline therapeutic decision-making, and ultimately improve patient outcomes [ 24 , 25 ]. Therefore, it is crucial to develop an iterative DL algorithm that can be effectively implemented in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Difficulties in the management of patients with rib fractures are becoming increasingly well recognized in the literature. 2 , 3 There is limited research supporting optimal respiratory physiotherapy or physical rehabilitation strategies for patients with rib fractures, and as a result, no consensus exists for physiotherapists/physical therapists managing this patient group. A global survey study investigating current physiotherapy management of patients with chest trauma reported that, although mobilization activities as a treatment strategy is commonly used in the acute phase of the injury, other interventions are diverse, and their impact on patient outcomes needs further exploration.…”
mentioning
confidence: 99%
“…Rib fractures account for more than 15% of all trauma admissions worldwide, with the most common injury mechanisms being low velocity falls, high velocity falls, road traffic collisions, assaults, and sporting injuries 1 . Difficulties in the management of patients with rib fractures are becoming increasingly well recognized in the literature 2,3 . There is limited research supporting optimal respiratory physiotherapy or physical rehabilitation strategies for patients with rib fractures, and as a result, no consensus exists for physiotherapists/physical therapists managing this patient group.…”
mentioning
confidence: 99%
“…4,5 These predictors include patient age, severity of injury, number and location of rib fractures, pre-injury anticoagulants, chronic lung disease and others. 4,[6][7][8] A common aim of such primary prognostic studies is the development of clinical prediction models. The clinical prediction model is intended to estimate the individualised probability or risk that a condition, for example mortality or pulmonary complications, will occur in the future by combining multiple prognostic factors / predictors from an individual.…”
mentioning
confidence: 99%